2012
DOI: 10.1016/j.bbamcr.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of apoptosis upon caspase-8 activation: Quantitative experimental validation of a mathematical model

Abstract: Caspase-8 (CASP8) is a cysteine protease that plays a pivotal role in the extrinsic apoptotic signaling pathway via death receptors. The kinetics, dynamics, and selectivity with which the pathway transmits apoptotic signals to downstream molecules upon CASP8 activation are not fully understood. We have developed a system for using high-sensitivity FRET-based biosensors to monitor the protease activity of CASP8 and its downstream effector, caspase-3, in living single cells. Using this system, we systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 87 publications
4
41
0
1
Order By: Relevance
“…The intrinsic and extrinsic pathways converge at caspase-3. Active caspases and 8 of the intrinsic and extrinsic pathways, respectively, have been shown to directly cleave and activate the effector protease caspase-3 (Kominami et al, 2012). In the present study, we have shown that caspases-3 and -7 are activated during BtxAmediated apoptosis.…”
Section: Discussionsupporting
confidence: 59%
“…The intrinsic and extrinsic pathways converge at caspase-3. Active caspases and 8 of the intrinsic and extrinsic pathways, respectively, have been shown to directly cleave and activate the effector protease caspase-3 (Kominami et al, 2012). In the present study, we have shown that caspases-3 and -7 are activated during BtxAmediated apoptosis.…”
Section: Discussionsupporting
confidence: 59%
“…11,28 Additionally, there is a higher concentration of initiator caspases versus executioner caspases in apoptotic cells. 29 Thus, excess concentrations of initiator caspases were used to ensure caspase-3 selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-8 proteolytically processes a downstream effector caspase-3 [99]. Once caspase-8 is activated, its downstream effector is channelized through receptors and termed as an extrinsic pathway [100]. However, intrinsic pathway is functionalized through entry of truncated Bid (tBid) into mitochondrion.…”
Section: Oleanolic Acid As Anticancer Agentmentioning
confidence: 99%